Analysis of Leadership, Job Satisfaction and Work Motivation on Employee Performance at PT. Maspion Medan - Nurul Fadilah; Siswa Pratama (International Journal of Management, Economic and Accounting, 2024)
The research analysis aims to determine the influence of leadership, job satisfaction, and motivation simultaneously on employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This study uses multiple linear regression analysis. The sample in this study was 64 respondents. Primary data collection uses questionnaires. The results of the study showed that the test results for the leadership variable showed a tcount value of 1.819 < ttable of 2.000 with a significant value of 0.017 > 0.05, then the H1 hypothesis was rejected and H0 was accepted, meaning that work leadership did not have a significant effect on employee performance partially. The test results for the job satisfaction variable showed a calculated value of 3.467 > a ttable of 2.000 with a significant value of 0.001 < 0.05, then the H2 hypothesis was accepted and H0 was rejected, meaning that job satisfaction had a positive and partially significant effect on employee performance. The test results for the work motivation variable showed a tcount value of 2.712 > a ttable of 2.000 with a significant value of 0.009 < 0.05, then the H3 hypothesis was accepted and H0 was rejected, meaning that work motivation had a positive and partially significant effect on employee performance. The simultaneous hypothesis test or F test proves that the value of F is calculated as 18.666 which is greater than 2.76 and the significant value of 0.000 is less than 0.05 so that it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so that it can be concluded that work motivation, job satisfaction and leadership have a significant simultaneous effect on employee performance.